Macropterous form of Paratrephes China, 1940, with new distributional records of Neotrephinae from Brazil (Hemiptera: Heteroptera: Helotrephidae) - Rodrigues, Higor D. D.; de Melo, Alan Lane; Ferreira-Keppler, Ruth L. (Zootaxa, 2012)
The subfamily Neotrephinae (Nepomorpha: Helotrephidae) includes two genera and is endemic to the Neotropical region. Paratrephes is monotypic and brachypterous specimens have been recorded from French Guiana, Suriname, Colombia, and Bolivia. Neotrephes has nine species and has been recorded from Argentina and Brazil. Presented here are a description of the macropterous form of Paratrephes hintoni China and the first records of this species from Brazil. In addition, Neotrephes lanemeloi Nieser & Chen is recorded for the first time from southern Brazil. Illustrations and a distribution map of both species are presented.